A study of skeletal remains using GlobalFiler™. Issue 1 (December 2019) - Almohammed, E.; Dragana, Zgonjanin; Hadi, S.
Abstract: DNA analysis from human remains is of immense relevance in missing persons identification and disaster victim identification (DVI). DNA degrades gradually in hard tissues, such as bones and teeth and remains somewhat safe from the effects of high temperature, humidity, pH, geochemical properties of the soil, and microorganisms. . The GlobalFiler™ kit simultaneously amplifies and detects 21 autosomal loci including CODIS extended set of STR loci. The kits was designed to combine all 21 autosomal STR loci along with a novel male speciﬁc Y insertion/deletion marker the sex-determining marker, amelogenin. Thus, GlobalFiler™ combines the CODIS extended set of loci and includes seven autosomal STR loci from the expanded European Standard Set of Loci (ESSL). The kit also includes the highly discriminating SE33 locus. The aim of this study was to profile the old skeletal remains using GlobalFiler™ for use in disaster victim identification that were previously profiled using Identifiler Plus kit using 3500 (CE). This study investigated the success rate of short tandem repeat (STR) typing from different types of bone samples and observed a higher STR success rate using GlobalFiler™ PCR kit, which contains more than 10 loci under 220 bp size. Thus, GlobalFiler™ could potentially be a good choice for the limited amounts of degraded DNA obtained from challenging skeletalsamples. The performance of the GlobalFiler™ kit and the profile quality was examined for the degraded bone samples to determine the robustness of genetic profiling.